Pengaruh Harga, Promosi, Dan Kualitas Pelayanan Terhadap Minat Penggunaan Ojek Online Grab - Yuni Yuniawati; Istichanah Istichanah (Universitas 45 Surabaya, 2023)
The purpose of this research is to find out whether there is an influence of price, promotion, service quality on interest in use. The population in this study are residents of Cimanggis District, Depok City who use online motorcycle taxi transportation service products from Grab. The data collection technique uses a questionnaire. The analytical tools used include Validity Test, Reliability Test, Multiple Linear Regression Analysis, F Test, T Test, Classical Assumption Test. The research results were declared valid and reliable based on the results of validity and reliability tests. From the results of the classical assumption test, multicollinearity and heteroscedasticity were not found. The equation obtained from the multiple linear regression test is, the independent variable that has the most influence on the dependent variable is price (0.467) followed by service quality (0.447) and promotion (0.104). Based on the results of the t test, price and service quality partially influence interest in use because it has a significance value of (0.001) while promotion partially has no effect on interest in use because it has a significance value of (0.520). Then, the results of the simultaneous test (F test) show that price, promotion and service quality simultaneously or simultaneously influence interes in using the Grab online motorcycle taxi service product.